2019
DOI: 10.1097/sla.0000000000003088
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Muscle Reinnervation Treats Neuroma and Phantom Pain in Major Limb Amputees

Abstract: Objective: To compare targeted muscle reinnervation (TMR) to “standard treatment” of neuroma excision and burying into muscle for postamputation pain. Summary Background Data: To date, no intervention is consistently effective for neuroma-related residual limb or phantom limb pain (PLP). TMR is a nerve transfer procedure developed for prosthesis control, incidentally found to improve postamputation pain. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
443
2
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 361 publications
(468 citation statements)
references
References 41 publications
5
443
2
18
Order By: Relevance
“…A recent randomized control trial for the treatment of established residual limb and neuroma pain in amputees with TMR versus neuroma excision and muscle burying showed improved PLP with TMR. 59 Furthermore, Serino et al 60 objectively demonstrated the beneficial effect of targeted muscle and sensory reinnervation on the normalization of motor and sensory cortical organization and the prevention of cortical reorganization that occurs after amputation, confirming similar findings by Chen et al 61 The potential for this strategy in the oncology population was recently highlighted. 62 With the recognition that chronic pain is difficult to treat, we have instituted TMR at the time of major limb amputation as routine practice at our institution, in particular for oncologic amputees, for the preemptive management of postamputation pain.…”
Section: Management Of Postamputation Pain Through Surgical Innovationmentioning
confidence: 56%
See 4 more Smart Citations
“…A recent randomized control trial for the treatment of established residual limb and neuroma pain in amputees with TMR versus neuroma excision and muscle burying showed improved PLP with TMR. 59 Furthermore, Serino et al 60 objectively demonstrated the beneficial effect of targeted muscle and sensory reinnervation on the normalization of motor and sensory cortical organization and the prevention of cortical reorganization that occurs after amputation, confirming similar findings by Chen et al 61 The potential for this strategy in the oncology population was recently highlighted. 62 With the recognition that chronic pain is difficult to treat, we have instituted TMR at the time of major limb amputation as routine practice at our institution, in particular for oncologic amputees, for the preemptive management of postamputation pain.…”
Section: Management Of Postamputation Pain Through Surgical Innovationmentioning
confidence: 56%
“…In a study focusing on the effect of TMR on postamputation neuroma pain, Souza et al demonstrated successful treatment of neuroma‐related symptoms in 93% of patients who had neuroma‐related pain before TMR. A recent randomized control trial for the treatment of established residual limb and neuroma pain in amputees with TMR versus neuroma excision and muscle burying showed improved PLP with TMR . Furthermore, Serino et al objectively demonstrated the beneficial effect of targeted muscle and sensory reinnervation on the normalization of motor and sensory cortical organization and the prevention of cortical reorganization that occurs after amputation, confirming similar findings by Chen et al The potential for this strategy in the oncology population was recently highlighted …”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations